ANALISIS KARAKTERISTIK NANOPARTIKEL PADA SEDIAAN SUSPENSI EKSTRAK ETANOL BUAH BAKAU MINYAK (RHIZOPHORA APICULATA) - Dwi Bagus; Wirasti; Achmad Vandian Nur (BENZENA Pharmaceutical Scientific Journal, 2025)
The ethanol extract of Rhizophora apiculata fruit was utilized in this study with the aim of formulating it into active nanoparticles, which were then prepared in the form of a suspension dosage and evaluated for stability. The nanoparticles were produced using the ionic gelation method, followed by particle characterization using a Particle Size Analyzer (PSA) and zeta potential measurement. The characterization results showed a particle size of 126.7 ± 2.170 nm, a polydispersity index of 0.601 ± 0.1005, and a zeta potential of 34.38 ± 0.2850 mV. Overall, these findings indicate that the Rhizophora apiculata fruit extract nanoparticles are stable and suitable for further development as a suspension dosage form.